Microporous scaffolds loaded with immunomodulatory lentivirus to study the contribution of immune cell populations to tumor cell recruitment in vivo. Issue 1 (3rd October 2019) - Bushnell, Grace G.; Rao, Shreyas S.; Hartfield, Rachel M.; Zhang, Yining; Oakes, Robert S.; Jeruss, Jacqueline S.; Shea, Lonnie D.
Abstract: Metastases are preceded by stochastic formation of a hospitable microenvironment known as the premetastatic niche, which has been difficult to study. Herein, we employ implantable polycaprolactone scaffolds as an engineered premetastatic niche to independently investigate the role of interleukin‐10 (IL10), CXCL12, and CCL2 in recruiting immune and tumor cells and impacting breast cancer cell phenotype via lentiviral overexpression. Lentivirus delivered from scaffolds in vivo achieved sustained transgene expression for 56 days. IL10 lentiviral expression, but not CXCL12 or CCL2, significantly decreased tumor cell recruitment to scaffolds in vivo. Delivery of CXCL12 enhanced CD45+ immune cell recruitment to scaffolds while delivery of IL10 reduced immune cell recruitment. CCL2 did not alter immune cell recruitment. Tumor cell phenotype was investigated using conditioned media from immunomodulated scaffolds, with CXCL12 microenvironments reducing proliferation, and IL10 microenvironments enhancing proliferation. Migration was enhanced with CCL2 and reduced with IL10‐driven microenvironments. Multiple linear regression identified populations of immune cells associated with tumor cell abundance. CD45+ immune and CD8+ T cells were associated with reduced tumor cell abundance, while CD11b+Gr1+ neutrophils and CD4+ T cells were associated with enhanced tumor cell abundance. Collectively, biomaterial scaffolds provide a tool to probe the formation and function of the premetastatic niche. Abstract : Metastases are preceded by stochastic formation of a hospitable microenvironment known as the premetastatic niche, which has been difficult to study. Herein, we employ implantable polycaprolactone scaffolds as an engineered premetastatic niche to independently investigate the role of interleukin‐10 (IL10), CXCL12, and CCL2 in recruiting immune and tumor cells and impacting breast cancer cell phenotype via lentiviral overexpression.